Commonly-used versus less commonly-used methods in the loss of resistance technique for identification of the epidural space: A systematic review and meta-analysis of randomized controlled trials - Carvalho, Larissa Pierri [UNESP]; Agarwal, Arnav; Kashiwagi, Flï¿½vio T [UNESP]; Corrï¿½a, Ione [UNESP]; Pereira, Josï¿½ Eduardo G [UNESP]; El Dib, Regina [UNESP] (Elsevier, 2017)
Study objective To summarize the efficacy of less-commonly used modern methods (e.g. epidrum, lidocaine, acoustic device, Macintosh balloon) compared to more commonly-used methods (i.e. air, saline, both) in the loss of resistance technique for identification of the epidural space. Design A systematic review. Setting A hospital-affiliated university. Measurements The following databases were searched: PubMed, CENTRAL, EMBASE, and LILACS. We used the GRADE approach to rate overall certainty of the evidence. Results Eight randomized trials including 1583 participants proved eligible. Results suggested a statistically significantly reduction in inability to locate the epidural space (RR 0.29, 95% CI 0.11, 0.77; Pï¿½=ï¿½0.01; I2ï¿½=ï¿½60%, risk difference (RD) 104/1000, moderate quality evidence), accidental intravascular catheter placement and accidental subarachnoid catheter placement (RR 0.35, 95% CI 0.21, 0.59; Pï¿½<ï¿½0.0001; I2ï¿½=ï¿½0%, risk difference (RD) 108/1000, moderate quality evidence), and unblocked segments (RR 0.37, 95% CI 0.18, 0.77; Pï¿½=ï¿½0.008; I2ï¿½=ï¿½0%, risk difference (RD) 56/1000, moderate quality evidence) with the use of epidrum, lidocaine, acoustic device, or modified Macintosh epidural balloon methods in comparison to air. Compared to saline, lidocaine presented higher rates of reduction in the inability to locate the epidural space (RR 0.31, 95% CI 0.12, 0.82; Pï¿½=ï¿½0.02; I2ï¿½=ï¿½not applicable). Conclusions Moderate-quality evidence shows that less commonly-used modern methods such as epidrum, lidocaine and acoustic devices, are more efficacious compared to more commonly-used methods (i.e. air, saline, both) in terms of the loss of resistance technique for identification of the epidural space. These findings should be explored further in the context of the clinical practice among anaesthesiologists.
Keywords: Acoustic device; Air; Epidrum; Grade; Lidocaine; Macintosh epidural balloon; Saline; Systematic review